Minor Effects of 11 Dof Family Genes Contribute to the Missing Heritability of Heading Date in Rice (Oryza sativa L.) - Huang, Yong; Han, Zhongmin; Cheng, Niannian; Luo, Meifang; Bai, Xufeng; Xing, Yongzhong (Frontiers in Plant Science, 2020)
DNA-binding with one finger (Dof) proteins are plant-specific transcription factors with important and diverse functions in seed germination, flowering time and biotic and abiotic stresses. In this study, haplotype-based association analysis was conducted between heading date and 30 Dof family genes in a worldwide germplasm collection. Of these, 22 Dof genes were associated with heading date. Multiple comparison among haplotypes revealed their diverse functions in promoting and suppressing heading date under short-day (SD) and long-day (LD) conditions. They cumulatively made a considerable contribution to the missing heritability of heading date. A set of knockout mutants of 30 Dof genes generated by CRISPR/Cas9-mediated genome editing technology showed that 11 Dof genes and 9 Dof genes regulated heading date under LD and SD, respectively. Phenotype measurement of mutants showed that these 11 Dof genes and 9 Dof genes slightly regulated heading with effects of 2-5 days under LD and SD, respectively. Both mutant and natural variation assays indicated functional redundancy in regulating heading date among Dof family genes. Nucleotide diversity analysis suggested that most Dof genes have been subjected to selection during domestication and improvement. Beyond heading date, this set of mutants is also a good resource for evaluating the function of Dof genes in regulating stress tolerance and seed germination.